2017
DOI: 10.18203/2320-6012.ijrms20174585
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Amylose and Amylopectin as indicators of glycaemic index and in vitro enzymatic hydrolysis of starches of long, medium and short grain rice

Abstract: Background: Rice (Oryzasativa L.) is the staple food of over half the world’s population. The major carbohydrate of rice is starch, which is about 72 to 75%. Rice can be classified into three different types: long-grain, medium-grain and short-grain rice based upon their length as compared to their width. Aim of the study was to predict the glycemic index of long, medium and short grain rice based on amylose, amylopectin ratio and to study in vitro hydrolysis of starch of long, medium and short grain rice by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…Hence, gamma irradiated rice could be beneficial for lowering blood glucose and can be used in the formulation of diets for diabetics. A comparative study on Indian long, medium, and short-grain rice ( Dipnaik and Kokare, 2017 ) reported that long-grain rice had high amylase, low amylopectin content, and higher Am/Ap ratio (1.12) which results in significantly slower in vitro starch digestibility using salivary and pancreatic amylase enzymes. Thus, the ratio of amylose and amylopectin has been established as the indicator affecting the rate and extent of starch hydrolysis and hence the glycemic response of the food.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, gamma irradiated rice could be beneficial for lowering blood glucose and can be used in the formulation of diets for diabetics. A comparative study on Indian long, medium, and short-grain rice ( Dipnaik and Kokare, 2017 ) reported that long-grain rice had high amylase, low amylopectin content, and higher Am/Ap ratio (1.12) which results in significantly slower in vitro starch digestibility using salivary and pancreatic amylase enzymes. Thus, the ratio of amylose and amylopectin has been established as the indicator affecting the rate and extent of starch hydrolysis and hence the glycemic response of the food.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Rayong 11 was the lowest for these traits for most planting dates except on 20 April in which it was equal to Kasetsart 50. The genotype with a higher content of amylose and ratio of amylose and amylopectin can be assumed to have a lower glycaemic index [47].…”
Section: Discussionmentioning
confidence: 99%
“…This can be done without affecting the palatability and without making major changes in the patient's eating preferences (Table 1). 10,12‐21 …”
Section: Healthy Eating In the Indian Settingmentioning
confidence: 99%
“…This can be done without affecting the palatability and without making major changes in the patient's eating preferences (Table 1). 10,[12][13][14][15][16][17][18][19][20][21] Fiber content of Indian diets can be increased by consuming whole grains (whole wheat, barley, broken wheat), millets, whole pulses (green gram, red gram, chickpea, and kidney beans), vegetables, salads, and fibrous fruits. Addition of dairy products (curd, cottage cheese or paneer), pulses, soybean, and egg can augment the protein content especially in those who cannot afford/do not eat meat, fish, or poultry.…”
Section: Improving the Glycemic Index And Protein Content Of Dietmentioning
confidence: 99%